Management of patients with multiple myeloma in the era of COVID-19 pandemic: a consensus paper from the European Myeloma Network (EMN) - Terpos, Evangelos; Engelhardt, Monika; Cook, Gordon; Gay, Francesca; Mateos, Maria-Victoria; Ntanasis-Stathopoulos, Ioannis; van de Donk, Niels W C J; Avet-Loiseau, Hervé; Hajek, Roman; Vangsted, Annette Juul; Ludwig, Heinz; Zweegman, Sonja; et al. (Leukemia, 2020)
Patients with multiple myeloma (MM) seem to be at increased risk for more severe COVID-19 infection and associated complications due to their immunocompromised state, the older age and comorbidities. The European Myeloma Network has provided an expert consensus statement in order to guide therapeutic decisions in the era of the COVID-19 pandemic. Patient education for personal hygiene and social distancing measures, along with treatment individualization, telemedicine and continuous surveillance for early diagnosis of COVID-19 are essential. In countries or local communities where COVID-19 infection is widely spread, MM patients should have a PCR test of nasopharyngeal swab for SARS-CoV-2 before hospital admission, starting a new treatment line, cell apheresis or ASCT in order to avoid ward or community spread and infections. Oral agent-based regimens should be considered, especially for the elderly and frail patients with standard risk disease, whereas de-intensified regimens for dexamethasone, bortezomib, carfilzomib and daratumumab should be used based on patient risk and response. Treatment initiation should not be postponed for patients with end organ damage, myeloma emergencies and aggressive relapses. Autologous (and especially allogeneic) transplantation should be delayed and extended induction should be administered, especially in standard risk patients and those with adequate MM response to induction. Watchful waiting should be considered for standard risk relapsed patients with low tumor burden, and slow biochemical relapses. The conduction of clinical trials should continue with appropriate adaptations to the current circumstances. Patients with MM and symptomatic COVID-19 disease should interrupt anti-myeloma treatment until recovery. For patients with positive PCR test for SARS-CoV-2, but with no symptoms for COVID-19, a 14-day quarantine should be considered if myeloma-related events allow the delay of treatment. The need for surveillance for drug interactions due to polypharmacy is highlighted. The participation in international COVID-19 cancer registries is greatly encouraged.
Keywords: Europe; Disease Management; koronavirové infekce; Infection Control; Multiple Myeloma; Practice Guidelines as Topic; Betacoronavirus; pandemie; SARS-CoV-2; Evropa; virová pneumonie; kontrola infekce; Time-to-Treatment; Telemedicine; lidé; Humans; telemedicína; Pneumonia, Viral; Pandemics; čas zasáhnout při rozvinutí nemoci; mnohočetný myelom; Coronavirus Infections; management nemoci; směrnice pro lékařskou praxi jako téma; COVID-19